STUDI PEMETAAN POLITIK DAN PERILAKU PEMILIH PADA PEMILIHAN UMUM KEPALA DAERAH DI KOTA PALEMBANG - Markoni Markoni (Politeknik Negeri Sriwijaya, 2014)
The research is aimed to explore political Map and voter behaviour. This research is to identify factors that influence voters in determining their choice to candidates. It is merely case study whereas the research are mainly focus on Major District General election in Palembang. The main research problems to be explored are concerning with the important factors that influence voters in determining their choice to candidates. The research mainly used primary data by delivering questionaires to selected respondents. The questionaire was delivered to 1070 selected respondents. It is also used secondary data to enrich the research analysis. Research finding shows that popularity and electability Romi Herton are higher among other candidats. It is also found that most voters are remain floating. In line with survey, newspaper is one of media used by voters as information sources that influence voters in determining their choice. the main factors effected voters in choosing Major candidates